MALWARE AVOIDANCE USING REDIRECTION TECHNIQUE - Al-janabi, Rana Jumaa Surayh (Al-Nahrain Journal of Science, 2010)
The Windows registry is behind almost every great feature in the operating system. Image fileexecution options (IFEO) is assumed as useful key in registry. In spite of that, malicious software(Malware) uses this key to convert a lot of system program's paths to their malicious code usingredirection technique. Actually, IFEO can be considered as a very important key that can be usedbeneficially or harmful to both.In this research, redirection technique is analyzed and used to build software that employ thisuseful key to provide helpful service by changing malware paths to illusion paths as preventivemethod in order to protect computer against attack by those malware. This software is designedusing assembly language and WinAsm to build friendly user interfaces